Lesson Study: An Approach to Increase the Competency of Out-of-Field Mathematics Teacher in Building the Students Conceptual Understanding in Learning Mathematics - Amirullah, Aini Haziah; Iksan, Zanaton H (FKIP-Universitas Riau, 2018)
The study was conducted to observe the effectiveness of LessonStudy as an approach used to increase the skills of an out-of-fieldMathematics teacher or ‘non-optional’ teacher, in building the conceptualunderstanding among students during the teaching and learning process. Thisqualitative case study was conducted using a Lesson Study approachinvolving a novice Mathematics teacher who is also a non-optional teacher,in a district of Seremban, Negeri Sembilan, Malaysia. An expert inMathematics, School Improvement Specialist Coach(SISC+) was involvedin the classroom observation. There were three different sessions conductedand the observation was recorded. Transcripts were prepared for the threeobservations for comparison and analytical review on the learning andteaching process with the Excellent Mathematics Teacher. It was observedthat the Mathematics teacher’s competency improved after evaluating thestudents’ response and achievements after the learning session. Teacherswho were involved,developed their skills and expertise through discussionsduring the Lesson Planning, teaching and review sessions. The teachers aremore confident in addressing students issue as well as class control ‘LessonStudy’ approach had contributed to upgrade the skills and efficiency of thenon-optional Mathematics teachers as well as enriching the learning strategy,approach and methodology.